PENGEMBANGAN MEDIA PEMBELAJARAN LARTANGYA (ULAR TANGGA BERNALAR MODEL POLYA) PADA MATERI BANGUN DATAR KELAS IV SEKOLAH DASAR - Prabowo, Satriyo Abid; Sulianto, Joko; Kiswoyo, Kiswoyo (Consilium: Education and Counseling Journal, 2025)
ABSTRACT: Media is part of the learning component, the benefits and functions of media in learning are felt by both teaching staff and students. The learning methods that are often used are theory, question and answer, demonstration learning and discussion, while teaching in class IV they rarely use interactive learning media, but still do it manually, during the learning process the children are less enthusiastic because they feel bored. The problem in this research is the availability of lartangya learning media and what are the results of validation tests and limited trials of lartangya learning media. The aim of this research is to find out how available the lartangya learning media is and what the results of validation tests and limited trials of lartangya learning media are. This research and development procedure implements the ADDIE procedure. The population in this study were fourth grade students at SDN 2 Pendem Grobogan. The data collection techniques used were pilot tests and questionnaires. The available Lartangya learning media can support learning material about flat shapes in class IV at SDN 2 Pendem Grobogan. Lartangya learning media produced an assessment from material experts and media experts of 96%. Where the score is listed between the intervals of 81%-100% in the "very feasible" category, which means that the Lartangya learning media is suitable for use as a learning media for class IV elementary school flat building material. Lartangya learning media produces assessments from trials on students. Group 1 got a score of 10 from the 3 questions they worked on, group 2 got a score of 10 from the 4 questions they worked on, group 3 got a score of 20 from the 5 questions they worked on, and group 4 got a score of 30 from the 7 questions they worked on.. Keywords: learning, polya, elementary school